CLASSROOM MANAGEMENT STRATEGIES FOR THEMATIC LEARNING IN PRIMARY SCHOOLS - Hermawan, Sesilya Karisma Dewi Ayu; Zira, Rangga Ade (Universitas Tanjungpura, 2024)
The purpose of this research is to know and understand how classroom management strategies are used by teachers in thematic learning in elementary schools. This research method uses the literature review method. Where the stages of this research are by identifying data, reviewing data, then analyzing, and presenting data. Thematic learning is an integrated learning model, where one learning theme is a combination of various subjects that require highlevel thinking skills, while classroom management is an effort made by teachers and schools to prepare everything related to teaching and learning activities for students, so as to create an effective, efficient, and conducive learning atmosphere. The main objective of classroom management is to create conducive learning conditions so that students can learn efficiently and effectively. Before learning is carried out, teachers will usually develop strategies such as classroom management strategies both non-physically and physically.The conclusion is that classroom management strategies have a major influence on the student learning process in order to achieve efficient and effective learning.